Debt-financed fiscal stimulus in South Africa - Hylton Hollander (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2021)
Debt-financed fiscal stimulus programmes directly stimulate aggregate demand through government expenditure or tax cuts, but their effectiveness is highly dependent on direct crowding out of private sector expenditure, spillover effects to the private sector through a higher risk premium on interest rates, and the interaction between fiscal policy and monetary policy. Using an open-economy fiscal dynamic stochastic general equilibrium model, we identify the effect of six different fiscal policy instruments (consumption spending, investment spending, transfers, consumption taxes, capital taxes, and labour taxes) on short-term and long-term (nominal and real) interest rates. These disaggregated expenditure and revenue shocks raise long-term real yields between 18 and 29 basis points, but there are non-negligible differences in the dynamic responses to each fiscal instrument. Our main findings suggest that, in the context of fiscal sustainability, an investment-driven debt-financed fiscal stimulus programme would reduce the government debtto-GDP ratio, especially in periods of economic slack when monetary policy would typically be more accommodative. In fact, since the global financial crisis, monetary policy has reduced the burden of fiscal adjustment in response to rising debt and a rising risk premium. But further shocks to the risk premium could offset any gains from the current stance of monetary policy (for example, a credit rating shock raises the long-term government bond rate 155 basis points). We conclude that if fiscal policy remains unsustainable a negative feedback loop between increasing debt-servicing costs (through a higher risk premium) and rapid debt accumulation may push the country into a sovereign debt crisis and economic distress.
Keywords: E43; E6; H3; H6; 330; government debt; interest rate; fiscal stimulus; fiscal sustainability